How Consumer's Demographics and Characteristics Influence Lunchtime Eating Behavior? (Case of Undergraduate Students in Bandung City) - Tsuruya, Yuki; Arai, Takeshi; Putro, Utomo Sarjono; Novani, Santi; Morimoto, Hidetsugu (SBM ITB, 2015)
Abstract. Â The current paper examined the level of food or store priorities of undergraduate students in Bandung City to promote better understanding of young generation in Bandung City. Based on two authors' theoretical foundation and Health Promotion Model, student's demographics, characteristics, food choice determinants, and store choice determinants are used as dimension that may consist of eating behavior. The questionnaire's survey of lunchtime eating behavior to the two universities, i.e., Institute Technology Bandung (ITB) and Parahyangan Catholic University (UNPAR) in Bandung City. The Selection of respondents took simple random sampling. Mann-Whitney U-test, Kruskal-Wallis test and ANOVA were used to examine the effect of consumer demographics and consumer characteristics for food and store choice determinants. A total of 251 undergraduate students participated; 54.6% were Males (n=137) and 45.4% were Females (n=114). Most of respondents were Moslem (48.4%) or Christian (40.6%). â€œCalorieâ€, â€œDegree of Congestionâ€, and Atmosphere (interior and exterior) were less important when they choose food or store. Moslem respondents tend to care food nutrient compared to the other religions. The result of this study is the priority of choosing food and store by respondents and showed national difference by using previous related research.Â Keywords: Eating Behavior, Food Choice Determinants, Store Choice Determinants, Bandung City, Undergraduate Students.Abstrak. Penelitian ini ditujukan untuk menganalisis perilaku konsumsi makanan khususnya generasi muda di Kota Bandung secara komprehensif. Melalui penelitian ini dihitung prioritas pilihan makanan dan tempat berbelanja makanan bagi mahasiswa. Demografi mahasiswa, karakteristik, determinan pilihan makanan, dan pilihan tempat berbelanja makanan menjadi dimensi yang akan menjelaskan tingkah laku untuk mengkonsumsi makanan pada para mahasiswa ini. Perilaku konsumsi makanan pada saat makan siang dilakukan dengan menyebarkan kuesioner Â melalui survei ke dua kampus di Bandung, yaitu Institut Teknologi Bandung (ITB) dan Universitas Katolik Parahyangan (UNPAR). Sedangkan untuk Statistika yang digunakan adalah Mann-Whitney U-test, Kruskal-Wallis test, dan ANOVA untuk menganalisis efek demografis konsumen dan karakteristik makanan yang dibeli, serta tempat berbelanja makanan yang dipilih. Survey dilakukan kepada 251 responden dengan proporsi 54.6% (n=137) laki-laki dan 45.4% (n=114) perempuan. Mayoritas responden adalah muslim (48.4%) dan Kristen (40.6%). Jumlah kalori, tingkat keramaian, dan suasana (interior dan eksterior) tidak terlalu diperhitungkan dalam memilih tempat berbelanja makanan. Hasil dari penelitian ini adalah prioritas memilih makanan dan tempat belanja oleh responden serta perbedaan secara nasionalis dengan menggunakan penelitian terdahulu yang berkaitan.Kata kunci: Perilaku konsumsi makanan, Determinan pilihan makanan, Determinan tempat berbelanja makanan, Indonesia, Mahasiswa